KOMITMEN ORGANISASI SEBAGAI PEMODERASI PENGARUH GOOD GOVERNANCE DAN PENGALAMAN KERJA PADA KUALITAS AUDIT - Rosiana Dewi, Desak Putu Kartika; Aryani Merkusiwati, Ni Ketut Lely (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of good governance’s understanding and work experience in audit quality along to determine whether organizational commitment will moderate the influence of good governance’s understanding and work experience in audit quality. This research was conducted in BPKP RI Representative Bali Province in 2015. Sampling of this study is method saturated sample. Methods of data collection is done by using survey methods. Data analysis techniques used are Multiple Linear Regression Analysis and Test MRA (Moderating Regression Analysis). Based on the analysis, it’s known that good governance’s understanding had positive effect on audit quality, while work experience had no effect on audit quality auditor of BPKP RI Representatives of Bali Province. The study also found that organizational commitment is able to strengthen the influence of work experience on the quality of audit but not able to moderate good governance’s understanding on audit quality.
Keywords: good governance’s understanding, work experience, commitment organizational auditor, audit quality